Invasive aspergillosis in patients with acute myeloid leukemia: difficulties in choosing first-line therapy in real clinical practice and pharmacoeconomic analysis of the feasibility of using new antifungal drugs - Yu. S. Osipov; A. A. Antonov; V. V. Ivanov; G. N. Salogub (Онкогематология)
The article discusses the epidemiology and difficulties of diagnosing invasive aspergillosis in patients with acute myeloid leukemia, the role of pharmacokinetic and pharmacogenetic studies in choosing the optimal treatment regimen, and an attempt at pharmacoeconomic analysis to create an optimal treatment strategy for this complication.